2019
DOI: 10.1016/j.amepre.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Prenatal Care by Presence and Type of Maternal Disability

Abstract: Introduction: Prior studies have found that women with disabilities are less likely to receive adequate prenatal care than women without disabilities. However, little is known about differences in patterns of prenatal care by type of disability. Therefore, this study examined timing and frequency of prenatal care among women with physical, sensory, or intellectual/developmental disabilities compared with women without disabilities. Methods: This was a retrospective cohort study using linked maternal and infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…Women with disabilities, particularly those with intellectual and developmental disabilities, enter prenatal care later than women without disabilities. 50,56,57,64,75 Perinatal care environments may be inaccessible, in terms of both the built environment (eg, examination tables that do not accommodate mobility limitations) and care delivery (eg, lack of interpreters for women with hearing impairments, complex medical terminology used with women with intellectual and developmental disabilities).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Women with disabilities, particularly those with intellectual and developmental disabilities, enter prenatal care later than women without disabilities. 50,56,57,64,75 Perinatal care environments may be inaccessible, in terms of both the built environment (eg, examination tables that do not accommodate mobility limitations) and care delivery (eg, lack of interpreters for women with hearing impairments, complex medical terminology used with women with intellectual and developmental disabilities).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Of the 16 included studies, eight were cross‐sectional 13,14,19‐24 and eight were retrospective cohorts 15,17,25‐30 . Studies were conducted in the United States ( n = 13) 13,15,17,19‐22,25‐30 and the United Kingdom (UK) ( n = 3) 14,23,24 and based on nine different data sources including: Massachusetts Pregnancy to Early Life Longitudinal data system (PELL, n = 3) 25‐27 ; California birth certificate and hospital discharge records ( n = 3) 15,17,29 ; Pregnancy Risk Assessment Monitoring System (PRAMS, n = 3) 13,21,22 ; and the UK National Health Service Care Quality Commission Survey ( n = 2) 14,23 . Definitions of physical disabilities varied.…”
Section: Resultsmentioning
confidence: 99%
“…Definitions of physical disabilities varied. Eight studies defined physical disabilities based on hospital records, databases, or diagnosis codes (eg International Classification of Diseases, ICD, codes): One study examined spinal cord‐related physical disabilities (eg spinal cord injury, spina bifida, paralysis) 28 and seven studies examined any diagnosed conditions related to physical disabilities (“diagnosed physical disabilities”) or grouped by body system (eg musculoskeletal, circulatory, nervous systems) 15,17,25‐27,29,30 . Two studies defined physical disability based on self‐report (“self‐reported physical disabilities”) 14,19 .…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Research to date has demonstrated disparities for women with disabilities in prenatal care utilization and satisfaction with prenatal care, preterm birth, having infants small for gestational age, and high rates of cesarean deliveries. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The majority of this research is based on delivery records or surveys like the Pregnancy Risk Assessment Monitoring System (PRAMS), which contain only live birth outcomes and therefore do not reflect early pregnancy loss or miscarriage. Thus, considerably less is known about the association between disability and miscarriage.…”
Section: Introductionmentioning
confidence: 99%